The effects of forward rotation of posture on computer-simulated 4-km track cycling: Implications of Union Cycliste Internationale rule 1.3.013. - Caddy, O.; Fitton, W.; Symons, D.; Purnell, A.; Gordon, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The aim of this research was to indicate improvements in 4-km cycling performance that may be gained as a function of reduced frontal surface area (A) when Union Cycliste Internationale rule 1.3.013 is contravened. In 10 male cyclists age 26 ± 2 (mean ± standard deviation)?years, height 180 ± 5 cm and body mass 71 ± 6 kg, entire cycling posture was rotated forward from where the nose of the saddle was 6 cm rearward of the bottom bracket spindle (P6) to 4, 2 and 0 cm (P4, P2 and P0); contravening Union Cycliste Internationale rule 1.3.013. Using computerised planimetry, A was estimated and a forward integration model was compiled to simulate 4-km track cycling end time (T4km) when a fixed power profile was applied. At P2, there was a significant but non-meaningful reduction compared to P6 (p < 0.05, d < 0.02). There were small but significant reductions in A and T4km between P6 and P0; -0.007 ± 0.004 m2 and -1.40 ± 0.73 s, respectively (p < 0.001, d = -0.259). There were no significant differences between P4 and P6 for A and T4km. These results suggest that at the most forward position (P0), a small but significant increase in 4-km performance can be expected compared to the legal position (P6). Moreover, the mean difference in T4km between P6 and P0 is greater than the winning margin at the Union Cycliste Internationale 4-km pursuit world championships four times in the previous 10 years.